A new species of Punctaltica from Guangdong, China (Coleoptera, Chrysomelidae, Galerucinae, Alticini) - Sun, Kexin; Ma, Liya; Ruan, Yongying; Liang, Zulong; Te, Nigeer; Liu, Yang (Zootaxa, 2025)
Punctaltica Ruan, Damaška, Konstantinov & Yang, 2025 (Coleoptera: Chrysomelidae: Galerucinae) is a distinctive genus named for the presence of numerous setiferous coarse punctures on sternum and frons of the head. It previously comprised only two species endemic to Guangdong Province, China. This study describes Punctaltica maculata Sun & Ruan, sp. nov., a new species characterized by large black spots on elytra, discovered from the Nanling National Nature Reserve in Shaoguan City, Guangdong Province. Images of external morphology and genitalia are provided. A key to all known species of Punctaltica is presented. Comparative diagnosis of the new species is discussed.